Comparing anadromous brown trout Salmo trutta in small, neighbouring catchments across contrasting landscapes: What is the role of environment in determining life‐history characteristics?. Issue 3 (7th February 2018) - Thomson, M.; Lyndon, A. R.
Abstract : Study of anadromous brown trout Salmo trutta in Orkney, U.K., burns (small streams) with a common‐garden sea in Scapa Flow supports the key role of nutrient availability in fresh water, independent of day length, as a determinant of smolt age, with a systematic increase in mean smolt age from 1 to 3 years related inversely to productivity. Whole catchment (8 km 2 ) population budgets indicated annual smolt production of around 650 individuals from approximately 100 spawners. Egg‐to‐smolt survival was 0·65%, while marine survival was estimated from mark–recapture to be between 3·5 and 10%. The question of B‐type growth (accelerated growth immediately prior to or during smolt migration) was also addressed, with a strong negative correlation between B‐type growth and size at end of winter suggesting that this represents a freshwater compensatory growth response. The data obtained indicate the potential importance of small catchments for supporting anadromous Salmo trutta populations and suggest that small runs of spawners (<100 individuals) are adequate to maintain stocks in such situations. Furthermore, they support the key role of freshwater productivity in determining life‐history characteristics over small spatial scales, with Orkney providing a useful natural laboratory for future research into metapopulation genetic structuring and environmental factors at a tractable scale.